New Perspectives in Forage Crops - Loiola Edvan, Ricardo; Rocha Bezerra, Leilson (IntechOpen, 2018)
In livestock management, the production of forage plants is undoubtedly the most efficient way to produce products of animal origin with quality and economic viability. We hope that the readers of the book "New Perspectives in Forage Crops" will have a good reading and appreciate the information provided on forage production, since the book draws on the expertise of different specialists of the area, who discuss the following aspects: fertilization, semiarid region production, forage species selection, nitrogen fixation, grasses, legumes, cacti, drought, etc. The authors of the book are of different nationalities and provide important information and diverse perspectives on the subject of forage farming.